Escalation and De-Escalation Strategies for Endocrine Therapy in Early-Stage Breast Cancer - Al-Batsh T; Abdel-Razeq N; Al-Masri Y; El-Khatib O; Sharaf B; Tamimi F; Abdel-Razeq H (Biologics: Targets & Therapy)
Tamer Al-Batsh,1 Nayef Abdel-Razeq,2 Yosra Al-Masri,1 Osama El-Khatib,1 Baha Sharaf,1 Faris Tamimi,1 Hikmat Abdel-Razeq1,3 1Section of Hematology and Medical Oncology, Department of Internal Medicine, King Hussein Cancer Center, Amman, 11941, Jordan; 2Department of Hematology and Medical Oncology, Mayo Clinic Florida, Jacksonville, FL, 32224, USA; 3School of Medicine, the University of Jordan, Amman, 11941, JordanCorrespondence: Hikmat Abdel-Razeq, Section of Hematology and Medical Oncology, Department of Internal Medicine, King Hussein Cancer Center, 202 Queen Rania Al Abdullah Street, P.O. Box: 1269, Amman, 11941, Jordan, Tel +962-6 5300460, Ext: 1000, Email habdelrazeq@khcc.joAbstract: Although adjuvant endocrine therapy (ET) greatly lowers the risk of recurrence and mortality in hormone receptor (HR)-positive early-stage breast cancer (EBC), more than 20% of patients may experience relapses within 10 years, often manifesting as incurable distant metastases. To improve outcomes, ovarian function suppression (OFS) with gonadotropin-releasing hormone agonists (GnRHa) added to tamoxifen or aromatase inhibitors like exemestane have shown significant disease-free survival (DFS) and, in some cases, overall survival (OS) benefits. CDK4/6 inhibitors, a cornerstone in metastatic HR-positive, HER2-negative breast cancer (MBC), are now being explored in EBC. Trials with abemaciclib and ribociclib have shown promise in high-risk EBC. For BRCA-mutant patients, the PARP inhibitor olaparib, as demonstrated in the OlympiA trial, significantly improved invasive DFS and OS when used as adjuvant therapy for one year. Conversely, de-escalation strategies are also emerging. Recent studies suggest that younger premenopausal women with low-risk disease may safely interrupt ET after 18– 30 months to pursue pregnancy. Additionally, genomic tumor profiling is widely utilized to decide on aggressiveness of adjuvant therapy of EBC. These advancements reflect a shift toward personalized adjuvant therapy, integrating targeted treatments like CDK4/6 inhibitors and PARP inhibitors, optimizing ET with OFS, and balancing efficacy with quality of life through de-escalation strategies. This tailored approach aims to improve long-term outcomes for HR-positive EBC patients.Keywords: breast cancer, endocrine therapy, ovarian function suppression, CDK4/6 Inhibitors, abemaciclib, ribociclib, aromatase inhibitors, tamoxifen, olaparib